ANALISIS STRUKTUR KALIMAT DALAM JURNAL THE POPULAR CULTURE STUDIES JOURNAL VOLUME 1 - MAMUDI, LOUIS SANTO JUSTINOLA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research is entitled â€œAnalisis Struktur Kalimat dalam Jurnal The Popular Culture Studies Journal Volume 1â€. It is a research which focuses on syntactic analysis, particularly the sentence structure analysis. In this analysis, the researcher attempts to analyse the structure of the sentences found in the journal by looking at the functions and categories of each sentenceâ€™s constituents. The data were collected in one of the articles in â€œThe Popular Culture Studies Journalâ€ entitled â€œWhen the Abyss Looks Back: Treatments of Human Trafficking in Superhero Comic Booksâ€. In identifying, classifying and analyzing the data, the researcher uses the theory of Aarts & Aarts (1982). The results of this research show that there are three types of sentence used in the article, namely simple, complex and compound sentences. The article consists of 97 simple sentences, 77 complex sentences, and 21 compound sentences. Furthermore, each type of sentence is divided into several subtypes. The simple sentences are divided into those which contain clauses and those which do not. The complex sentences are divided based on the functions realized by the subordinate clauses. There are direct object clauses, subject attribute clause, object attribute clauses, predicator complement clauses and adverb clauses. There are no complex sentences which contain subject clause, indirect object clause, benefactive object clause. The compound sentences are divided into the combination of simple sentences, the combination of simple and complex sentences, and the combination of complex sentences. The results also show that every sentence contains, at least, one subject and one predicate. Some sentences also contain adverbs.Â This research is expected to give contributions in the development of linguistic studies, particularly in syntactic analysis. It is also expected to help the readers to have knowledge on the sentence structure analysis. Â Â Keywords: Syntax, Types of Sentence, Sentence Structure Analysis, The Popular Culture Studies Journal Volume 1